Revisiting the volatility-growth relationship: Some cross country evidence, 1978-2017 - Y. N. Raju; Debashis Acharya (Cogent Economics & Finance, 2020)
This paper attempts a re-examination of the relationship between the output volatility and economic growth using an annual data set for select 67 countries for the period 1978 to 2017 spanning over 40 years. Towards this objective cross section and panel, regressions are estimated for different country groups namely developing, industrial, high financially integrated (HFI) and low financially integrated (LFI) country groups. Overall, the results indicate that output volatility as a proxy of macroeconomic volatility has negative effect on economic growth. The results appear to be stronger when we include other control variables as part of an information set. The panel regression results support the negative relationship between economic growth and volatility for the developing countries. The financial development indicator indicates significant relation with growth for industrial economies.
Keywords: C1; C3; F15; F36; F41; F43; G24; 330; economic growth; financial development; growth volatility; HP filter